Evaluating cultivars of 3 vegetable crops for inclusion in a food security systems - Dayzie, Daryline (Kansas State University, 2023)
The important practices of Indigenous food sovereignty must be restored! Restoration of Indigenous foodways ensures the continuation of the historical lineage of heirloom seeds and preserves the cultural background that tribal nations carry. Citizens of tribal nations continue to face environmental conditions that create scarcity in heirloom vegetable production. Modern vegetable breeding, particularly hybridization, has been the key to improve yield, shelf life, pest resistance, and environmental durability. The purpose of this research is to understand and compare field production of heirloom and hybrid tomatoes (Solanum lycopersicum) ‘Cherokee Purple’ vs. ‘Medusa’, Anaheim- chili peppers (Capsicum annuum) ‘Anaheim 118’ vs. ‘Charger’ and Butternut squash (Cucurbita moschata). ‘Neck Pumpkin’ vs. ‘Waltham’ vs ‘Avalon’ vs. ‘Paula’. In addition to yield, the shelf life and Brix sugar content of butternut squash was recorded Limited irrigation was applied to the production plots to mimic the dry Arizona conditions of my home community. The Navajo Nation is the largest tribal nation in the United States and sprawls into northeastern Arizona, northwest New Mexico and southeast Utah. Water management is based in the central agencies of the Navajo Nation, where citizens face drought concerns yearly and farmers rely heavily on the monsoon season. However, this research was conducted at Kansas State University’s Willow Lake Student Farm, where soil conditions are finer textured loam compared to the sandy soils of Arizona. Also, eastern Kansas experiences a much more abundant summer rainfall as compared to Arizona. The observed yield data from the tomatoes and peppers showed no significant difference between heirloom and hybrid cultivar production. Although yield data from the squash production concluded that the heirloom ‘Neck Pumpkin’ produced twice as much weight as the other cultivars, including open-pollinated ‘Waltham’ and hybrids ‘Avalon’ and ‘Paula’. ‘Neck Pumpkin’ also had the highest yield by count for 2021, but ‘Waltham’ had a slightly higher yield count but not significantly different from ‘Neck Pumpkin’ for 2022. Tomato mulch treatments showed no significant differences in yield, but field observations showed the benefits of mulch reducing weeds and retaining moisture when tomatoes and peppers experienced drought stress. Additionally, the research can offer an informative background for Tribal Nations to encourage the continuation of heirloom production and tribal teachings. The project integrated tribal teachings from the outset and utilized the Three-Sisters demonstration. Seeds used for the Three-Sister Garden included Navajo and Pima Blue corn with Kentucky Blue beans and pitcher gourd, all planted in a circular pattern in the corners of the research plot. This demonstration illustrates the importance of companion planting and highlights the positive outcomes of practicing cultural teachings.
Keywords: Vegetables production; Mulch treatment; Limited irrigation; Squash; Tomatoes; Peppers